Alexander Hamilton Stephens papers - Stephens, Alexander Hamilton, 1812-1883.
Correspondence, memoranda, telegrams, journal, autobiography, legal documents, clippings, and other papers reflecting Stephens's career in government and politics. Chiefly correspondence concerning national and sectional questions as well as local affairs, philanthropy, and plantation management. Subjects include the presidential election of 1876; Civil War; Compromise of 1850; formation and operation of the Confederate Government; Dred Scott decision; Indian affairs; Kansas-Nebraska Act; political parties including the American Party (Know-Nothing Party), Democratic Party, Republican Party (1854- ), and Whig Party; Reconstruction; secession; slavery; states' rights; territorial expansion; and annexation of Texas. Other subjects include education, tariff, transportation, and other economic, literary, political, and social matters. Includes letters from Stephens's slaves. Other correspondents include Francis Preston Blair, Joseph E. Brown, Fitzwilliam Byrdsall, Henry Cleveland, Howell Cobb, A.H. Garland, John Brown Gordon, Paul Hamilton Hayne, William H. Hidell, Henry R. Jackson, Herschel V. Johnson, Richard Malcolm Johnston, L.Q.C. Lamar, James Ryder Randall, J. Henley Smith, Robert Augustus Toombs, James I. Waddell, and Ambrose R. Wright.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Lawyer, journalist, governor of Georgia, U.S. senator and representative from Georgia, and vice president of the Confederate States of America.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Blair, Francis Preston, -- 1791-1876 -- Correspondence; Brown, Joseph E. -- 1821-1894 -- Correspondence; Byrdsall, Fitzwilliam, -- 1810-1875? -- Correspondence; Cleveland, Henry -- Correspondence; Cobb, Howell, -- 1815-1868 -- Correspondence; Garland, A. H. -- 1832-1899 -- Correspondence; Gordon, John Brown, -- 1832-1904 -- Correspondence; Hayne, Paul Hamilton, -- 1830-1886 -- Correspondence; Hidell, William H. -- Correspondence; Jackson, Henry R. -- 1820-1898 -- Correspondence; Johnson, Herschel V. -- 1812-1880 -- Correspondence; Johnston, Richard Malcolm, -- 1822-1898 -- Correspondence; Lamar, L. Q. C. -- 1825-1893 -- Correspondence; Randall, James Ryder, -- 1839-1908 -- Correspondence; Scott, Dred, -- 1809-1858 -- Trials, litigation, etc; Smith, J. Henley, -- 1829- -- Correspondence; Toombs, Robert Augustus, -- 1810-1885 -- Correspondence; Waddell, James I. -- 1824-1886 -- Correspondence; Wright, Ambrose R. -- 1826-1872 -- Correspondence; United States; American Party; Confederate States of America; Democratic Party (U.S.); Republican Party (U.S. : 1854- ); Whig Party (U.S.); American literature -- 19th century; Charities; Compromise of 1850.; Education -- United States; Elections -- United States -- 1876.; Indians of North America -- Government relations; Plantations -- Georgia; Political parties -- United States; Reconstruction (U.S. history, 1865-1877); Secession; Slavery -- Law and legislation -- United States; Slavery -- Georgia; Slaves -- Georgia -- Correspondence; States' rights (American politics); Tariff -- United States; Transportation -- United States; Confederate States of America -- History; Confederate States of America -- Politics and government; Georgia -- History -- 1775-1865.; Georgia -- History -- 1865-; Georgia -- Politics and government -- 1775-1865.; Georgia -- Politics and government -- 1865-1950.; Southern States -- History -- 1865-1877.; Texas -- Annexation to the United States; United States -- Economic conditions; United States -- History -- Civil War, 1861-1865.; United States -- History -- 1865-1898.; United States -- Politics and government -- 19th century; United States -- Social conditions; United States -- Territorial expansion; Governors -- Georgia; Journalists; Lawyers; Representatives, U.S. Congress -- Georgia; Senators, U.S. Congress -- Georgia